ANALYSIS OF POLYCYCLIC AROMATIC HYDROCARBONS (PAH) COMPOUNDS FROM SEDIMENT IN THE WATERS KAYU BANGKOA PORT AND DEGRADATION OF PHENANTHRENE IN SEDIMENT BY USING KMNO4 OXIDIZER - Tiameisetia Sumomba; Nursiah La Nafie; Adiba Arief (Marina Chimica Acta, 2017)
Research about analysis of Polycyclic Aromatic Hydrocarbon (PAH) from sediments in water of Kayu Bangkoa Port and degradation of phenanthrene from sediments by using KMnO4 have been conducted by Gas Chromatography Mass Spectrophotometry (GC-MS). The samples of sediment were taken at three location in the waters of the Kayu Bangkoa Port. Measurements of phenanthrene performed by standard internal method and analyzed using GC-MS. The results show that KMnO4 oxidizing agent capable of degradated the whole phenanthrene with concentration of 137,13 ng/g in sediment